1997
DOI: 10.1002/art.1780401219
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial outcomes and health status of adults who have had juvenile rheumatoid arthritis. A controlled, population‐based study

Abstract: Objective. The goal of this study was to evaluate the physical and psychosocial impact of juvenile rheumatoid arthritis (JRA) among a population‐based cohort of adults who had the disease during childhood, compared with a control cohort of subjects with no history of JRA. Methods. The Rochester Epidemiology Project database was used to identify all cases of JRA (based on the American College of Rheumatology [formerly, the American Rheumatism Association] 1977 criteria) among Rochester, Minnesota residents firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
102
6
13

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 19 publications
13
102
6
13
Order By: Relevance
“…A significant relationship between clinical depression and anxiety on psychological testing and the degree of disability was found by David et al (27). In a populationbased study, Peterson et al (28) reported that their JIA cohort perceived poorer health, less energy, more bodily pain, and more limitation in physical functioning compared with healthy children. Foster et al (29) recorded significantly worse scores than healthy controls in all physical scales and in the emotional role scale of the HRQOL measure in adults who had JIA.…”
Section: Discussionmentioning
confidence: 89%
“…A significant relationship between clinical depression and anxiety on psychological testing and the degree of disability was found by David et al (27). In a populationbased study, Peterson et al (28) reported that their JIA cohort perceived poorer health, less energy, more bodily pain, and more limitation in physical functioning compared with healthy children. Foster et al (29) recorded significantly worse scores than healthy controls in all physical scales and in the emotional role scale of the HRQOL measure in adults who had JIA.…”
Section: Discussionmentioning
confidence: 89%
“…Although it has often been assumed that children outgrow JIA, recent evidence has indicated that many children have recurrent disease into adulthood and long-term physical symptoms vary widely (2)(3)(4)(5). While some adults with JIA have reported few problems, others have noted reduced physical functioning, vision problems, greater pain, more fatigue, and poorer overall health compared with individuals without the disease (2,(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Although youths with arthritis may be at risk for internalizing symptoms (9), multiple studies have suggested that they generally do not have severe or lasting psychopathology (10 -14). As a result, research has focused on developmental milestones or life goals as more subtle indicators of functioning (5,8,15). A primary milestone for youth is the transition out of high school into training and education for a future occupation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations